Factors influencing customers visiting shopping malls in Kuala Lumpur / Azlina Shahabuddin and Noor Rosnani Osman - Shahabuddin, Azlina; Osman, Noor Rosnani (Faculty of Business and Management, 2015)
The objective of this study is to examine the relationship between four hypotheses which is the relationship between convenience, diversity, comfort and facility with shopping malls in Kuala Lumpur. For this purpose of this study, the descriptive research was deployed. Convenient sampling has been utilised with 150 respondents as the sample size which 100 usable questionnaires were answered and collected from the respondents based on their consent and voluntary basis. The result revealed that all of the hypotheses shows a positive relationship and significant between each other. As recommendations, the mall management should provide a pleasant environment for shoppers and provide more facilities especially for disabled person. Other recommended independent variables are mall essence and edutainment. By using the analysed generated by SPSS (Statistical Package for Social Science), results are analysed and deductions being drawn. Finally, the findings from this study will make shopping malls the first choice in order to capture the shoppers’ attention towards the factors that influence customers visiting shopping malls in Kuala Lumpur.